Q: Put the equation in the form ax2 plus bx plus c equals 0 x2-3 equals 3x2 plus 8x?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0

(a) y = -3x + 1

Set the equation equal to zero. 3x2 - x = -1 3x2 - x + 1 = 0 The equation is quadratic, but can not be factored. Use the quadratic equation.

The equation is equivalent to: -3x2 - 12x - 1 = 0 [you could change signs to get 3x2 + 12x + 1 = 0 but that is not required] The discriminant is (-12)2 - 4*(-3)(-1) = 144 - 12 = 132

With difficulty because it's not an equation but an expression.

Related questions

3x2 + 17x + c = 0, rearranging gives c = -3x2 - 17x

y2=x3+3x2

x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0

56

2

No. Y=3X2+1 is a Binomial Equation.

y2-3x2+6x+6y= 18 is in standard form. The vertex form would be (y+3)2/24 - (x-1)2/8 = 1

It has one double solution.

(a) y = -3x + 1

3x2 + 2x - 8 = 0 is a quadratic equation.

3x2=6+38=44

It is: 3x2-5x-2 = 0 and the value of x is -1/3 or 2 when solved